Combating greenwashing through public critique. Issue 2 (2nd April 2016) - Prody, Jessica M.
Abstract : Courses: Environmental Communication, Environmental Media, or Critical Media Studies courses Objectives: This unit activity is designed to guide students in a critical examination of advertising that utilizes green appeals to sell products or brands. The assignment asks students to use concepts from media analysis, communication ethics, and social justice to critique advertising claims and potential influences of advertising on society's environmental discourse. Students should be able to identify greenwashing in advertisements, research whether the statements of the advertisements are accurate, and discuss the significance of the advertisements' messages in shaping environmental and social thought. A secondary purpose of the assignment is to give students experience writing for a popular audience in a public forum.